Absence of Maternal Microchimerism in Regional Lymph Nodes of Children With Biliary Atresia. Issue 6 (June 2016) - Engelmann, Carsten; Maelzer, Madeleine; Kreyenberg, Hermann
ABSTRACT: Objective: Maternal lymphocytes have been cited as a potential cause of infantile biliary atresia (BA). When hepatoportoenterostomy is performed, locoregional lymphadenopathy is frequently encountered. Methods: We screened enlarged nodes from 6 consecutive nonsyndromatic BA patients (age: 68 days ± 18.9 days) for maternal elements using DNA fingerprinting with short tandem repeat analysis and quantitative real-time polymerase chain reaction for allelic (single nucleotide) sequence polymorphisms. Results: Although being partly positive in infants' peripheral blood, no maternal microchimerism could be demonstrated in any of the lymph nodes. Conclusion: This result challenges the hypothesis that maternal cells play a role in hilar lymphadenopathy of children with BA.